Inter-annual and site-specific variability in greenhouse gas emissions from linseed genotypes - Walthall, Conor; Johnston, Alice S. A.; Kevei, Zoltan; Padbury, Nigel; Girkin, Nicholas T. (Frontiers, 2026)
Agriculture contributes significantly to global greenhouse gas (GHG) emissions. With increasingly diverse rotations, interest is growing in break crops such as linseed (Linum usitatissimum L.) to support soil health, pest and disease control, and reduce nitrogen inputs. However, the controls on GHG emissions (CO2, CH4, N2O) from linseed, particularly genotypic variation, remain poorly understood. This study investigated genotypic variations in GHG emissions among four elite linseed genotypes (Empress, Omegalin, Richess, VT50) at two UK field sites: Leicestershire (Ashby-de-la-Zouch) in 2024 and Derbyshire (near Elvaston) in 2025. Using closed static chambers connected to a Gasmet GT5000 portable FTIR analyser, weekly GHG fluxes, soil temperature, volumetric soil moisture, and crop height were measured in randomised plot designs under commercial fertiliser regimes. Cumulative emissions were calculated by trapezoidal integration of daily mean fluxes, and data were analysed with ANOVA and linear mixed-effects models. Significant site- and year-driven differences in overall GHG emissions were observed (P < 0.05), with markedly higher cumulative CO2, N2O and CH4 fluxes in the warmer, wetter 2024 season. No significant genotypic differences were found in cumulative CO2 or N2O emissions. However, genotype VT50 exhibited a significant CH4 sink (–2.83 g ha-1) in 2025. Crop height varied significantly between sites (P < 0.001) and positively influenced CO2 fluxes (P < 0.05), with interactive effects of height × soil temperature on CO2 and height × volumetric moisture on CH4 and N2O fluxes (P < 0.05). Environmental factors (site, climate, and management) dominated over genotype in determining GHG emissions from linseed under field conditions. VT50 showed strong potential for low-emission production, particularly as a CH4 sink in certain years. These findings highlight the value of integrated genetic and environmental strategies, including growth-optimised genotypes, to enhance break crops like linseed for net-zero and sustainable agriculture.
Section on Climate-Smart Agronomy
Keywords: 30 Agricultural, Veterinary and Food Sciences; 3004 Crop and Pasture Production; 41 Environmental Sciences; 13 Climate Action